1999
DOI: 10.1523/jneurosci.19-09-03594.1999
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Neuronal Activity and Responsiveness to Dopamine and Glutamate after Selective Blockade of D1 and D2 Dopamine Receptors in Freely Moving Rats

Abstract: Although striatal neurons receive continuous dopamine (DA) input, little information is available on the role of such input in regulating normal striatal functions. To clarify this issue, we assessed how systemic administration of selective D1 and D2 receptor blockers or their combination alters striatal neuronal processing in freely moving rats. Single-unit recording was combined with iontophoresis to monitor basal impulse activity of dorsal and ventral striatal neurons and their responses to glutamate (GLU),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 64 publications
(73 reference statements)
11
61
1
Order By: Relevance
“…Thus, DA enhances the relative rather than absolute strength of the GLU signal. Further testing revealed that endogenous DA exerts this effect mainly via D1 receptors (Kiyatkin and Rebec, 1999b). In fact, with D1 receptor blockade, striatal neurons become hyper-responsive to GLU.…”
Section: Behavior-related Transmitter Interactionsmentioning
confidence: 98%
“…Thus, DA enhances the relative rather than absolute strength of the GLU signal. Further testing revealed that endogenous DA exerts this effect mainly via D1 receptors (Kiyatkin and Rebec, 1999b). In fact, with D1 receptor blockade, striatal neurons become hyper-responsive to GLU.…”
Section: Behavior-related Transmitter Interactionsmentioning
confidence: 98%
“…It is noteworthy that, in the presence of raclopride, an increase in NMDA concentration up to 10 lM led to extinction of the NMDA effect. This may be related to a depolarization inactivation of projection neurons (Hu and White 1996), which is enhanced by D 2 receptor antagonism (Kiyatkin and Rebec 1999).…”
Section: )mentioning
confidence: 99%
“…slices). Recently, studies employing DA receptor antagonists in vivo have shown that D 1 and D 2 receptors tonically modulate the excitability of striatal GABAergic neurons and their responsiveness to glutamate (GLU; Kiyatkin and Rebec 1999;West and Grace 2002). The capability of NMDA to release striatal GABA in vivo is also differentially modulated by DA receptor antagonists (Morari et al 1994).…”
mentioning
confidence: 99%
“…Both drugs were obtained from Sigma (St. Louis, MO), freshly dissolved, mixed, and injected subcutaneously. Neuronal data obtained between 20 min and 3 h following the injection of DA antagonists were accepted as occurring during full DA receptor blockade, as confirmed by the antagonism of striatal neuronal responses to iontophoretic DA (Kiyatkin and Rebec, 1999). DA blockade was maintained by additional injection of DA antagonists at half the dose, three hours after the initial administration.…”
Section: Experimental Protocolmentioning
confidence: 79%
“…Therefore, similar to our previous study, recordings were performed in animals administered with a mixture of D1-and D2-selective antagonists (SCH233900 and eticlopride), providing an effective blockade of DA transmission. DA receptor blockade greatly attenuates cocaine-induced motor activation, thus allowing artifact-free neuronal recording, but it keeps neuronal responses to sensory stimuli relatively intact (Kiyatkin and Rebec, 1999;Kiyatkin and Brown, 2007). The use of DA antagonists also excludes any possible contribution of DA mechanisms to the observed neuronal responses to sensory stimuli and cocaine.…”
Section: Introductionmentioning
confidence: 99%